Synthesis of C(60) Fullerene–Quadricyclane Hybrid Compound and Its Preliminary In Vitro Antitumor Activity in Combination with Cisplatin - Dzhemilev, Usein M. (ACS Omega, 2019)
[Image: see text] This paper describes the authors’ preliminary studies directed toward the possibility of the practical implementation of the idea to design efficient antitumor drugs based on hybrid molecules composed of fullerene C(60) and quadricyclanes. The essence of the proposed idea is that these hybrid molecules are able to cleave DNA owing to the fullerene moiety they contain and to simultaneously thermally affect tumor cells via cleavage of the carbon–carbon bond in quadricyclanes under the action of Pd and Pt ions. As a result, testing of the cytotoxic activity in vitro for a number of fullerene C(60) hybrids with the norbornadiene or quadricyclane moieties against the human T-lymphoblastic leukemia cells (Jurkat cells) in combination of the known cisplatin drug, which was taken as the source of Pt ions, showed a statistically reliable dose-dependent increase in the number of dead cells in each group, which were formed according to the amount of cisplatin added, in comparison with the control, that is, cells treated with cisplatin or quadricyclane fullerene derivatives alone. Indeed, the difference between the percentages of viable cells after treatment with either cisplatin alone or cisplatin in combination with methanofullerene 5 ranged from ∼10% (for Pt (0.015 mkM), 5 (0.015 mkM)) to ∼55% (for Pt (0.03 mkM), 5 (0.045 mkM)).